2006
DOI: 10.1136/emj.2005.029397
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pulmonary embolism with CT pulmonary angiography: a systematic review

Abstract: Objective: To appraise the evidence on the diagnostic accuracy of CT pulmonary angiography and the prognostic value of a negative CT pulmonary angiogram in the diagnosis of pulmonary embolism. Methods: Medline, EMBASE, and grey literature were systematically searched by two researchers. Any study which compared CT pulmonary angiography to an acceptable reference standard or prospectively followed up a cohort of patients with a normal CT pulmonary angiogram was included. Study methods were appraised independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 45 publications
(35 reference statements)
1
38
0
2
Order By: Relevance
“…The 9 reviews included 33 primary studies, of which 8 studies were most consistently included across reviews. The newest reviews, 59,[66][67][68] published in 2005 and 2006, included studies published since 2000, which were not included in the earlier reviews. Only 1 review included the study by Winer-Muram, which used multidetector CT. 69 The systematic reviews reported a wide range of summary sensitivities (66%-93%), with only 1 review reporting a summary sensitivity of greater than 90%.…”
Section: Helical Ct What Are the Test Characteristics Of Helical Ct Fmentioning
confidence: 99%
See 3 more Smart Citations
“…The 9 reviews included 33 primary studies, of which 8 studies were most consistently included across reviews. The newest reviews, 59,[66][67][68] published in 2005 and 2006, included studies published since 2000, which were not included in the earlier reviews. Only 1 review included the study by Winer-Muram, which used multidetector CT. 69 The systematic reviews reported a wide range of summary sensitivities (66%-93%), with only 1 review reporting a summary sensitivity of greater than 90%.…”
Section: Helical Ct What Are the Test Characteristics Of Helical Ct Fmentioning
confidence: 99%
“…61,62 Five reviews included only prospective studies. [62][63][64]66,68 The description of search methods was generally the weakest element across systematic reviews (Supplemental Appendix 4, available online at http:// www.annfammed.org/cgi/content/full/5/1/63/ DC1). The 9 reviews included 33 primary studies, of which 8 studies were most consistently included across reviews.…”
Section: Helical Ct What Are the Test Characteristics Of Helical Ct Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Imaging and analyzing these structures is important for diagnostic purposes. As an example, computer tomography angiography (CTA) is now a standard clinical tool for diagnosing coronary artery diseases (Weustink and de Feyter, 2011;Marwan et al, 2014) and pulmonary embolism (Mos et al, 2009;Hogg et al, 2006). Magnetic resonance angiography (MRA) is used clinically for imaging the cerebral vessels (Parker et al, 1998) as well as the renal and peripheral arteries (Dong et al, 1999;Prince et al, 1999).…”
Section: Introductionmentioning
confidence: 99%